2012
DOI: 10.1021/ja207899j
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Solution and Gas-Phase Reactions of the Three Distonic Isomers of the Pyridine Radical Cation with Methanol

Abstract: In order to directly compare the reactivity of positively charged carbon-centered aromatic σ-radicals toward methanol in solution and in the gas phase, the 2-, 3-, and 4-dehydropyridinium cations (distonic isomers of the pyridine radical cation) were generated by ultraviolet photolysis of the corresponding iodo-precursors in a mixture of water and methanol at varying pH. The reaction mixtures were analyzed by using liquid chromatography/mass spectrometry. Hydrogen atom abstraction was the only reaction observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Another reaction seen with t-butyl isocyanide is the addition of +26 Da corresponding to the abstraction of a cyano group by the radical cation. This abstraction is the second major product during reaction with the 2-mercaptopyridyl radical ion (10), and a less significant product in reaction with the 2-mercaptopyrimidyl radical cation (9). This reaction has been seen before when t-butyl isocyanide was used in IMR reactions of carbon-centered radicals [65,67,68].…”
Section: (9)mentioning
confidence: 70%
See 2 more Smart Citations
“…Another reaction seen with t-butyl isocyanide is the addition of +26 Da corresponding to the abstraction of a cyano group by the radical cation. This abstraction is the second major product during reaction with the 2-mercaptopyridyl radical ion (10), and a less significant product in reaction with the 2-mercaptopyrimidyl radical cation (9). This reaction has been seen before when t-butyl isocyanide was used in IMR reactions of carbon-centered radicals [65,67,68].…”
Section: (9)mentioning
confidence: 70%
“…These products are depicted in Eq. (10). (10) The radical cations 7-10 favored the +75 Da addition over the +1 Da.…”
Section: Reactions With 1-propanethiolmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the atomic charges of 2-, 3-, and 4-pyridyl radical site (+0.015, −0.268, and −0.007, respectively) have been calculated at the BPW91/cc-pVDZ// BPW91/cc-pVDZ. 11 In this paper, it is revealed that 2-pyridyl radical with a partial positive charge behaves like an electrophilic radical, but 3-and 4-pyridyl radical behave like a nucleophilic radical. And, the relative energies of 2-, 3-, and 4-pyridyl radical (0, 26, and 21 kJ/mol, respectively) have been calculated by G3B3…”
mentioning
confidence: 94%
“…Recent studies have shown that charged radicals behave similarly in the gas phase and in solution [10].…”
Section: Introductionmentioning
confidence: 99%